SIMBOLIS ATAU SUBSTANTIF? ANALISIS PRAKTIK PELAPORAN CSR DAN KUALITAS PENGUNGKAPAN - Nasution, Ryan Muhammad; Adhariani, Desi (Jurnal Akuntansi dan Keuangan Indonesia, 2016)
This research is aimed to test empirically the influence of three Corporate Social Responsibility reporting (CSR) practices on the quality of CSR disclosure. Specifically, the research is conducted to determine whether the practices are substantive in nature, which is to improve the quality of disclosure as media of accountability to stakeholders; or simply symbolic to establish a company’s positive image. The three practices are the use of standalone CSR reports, Global Reporting Initiative (GRI) frameworks, and external assurance services for CSR reports. This study uses a sample of 50 non-financial companies with large market capitalization listed in Indonesia Stock Exchange in 2011-2013. The results show that the use of standalone CSR reports negatively affects the quality of CSR disclosure, which is interpreted as a reflection of the symbolic approach in its preparation. Meanwhile, the use of external assurance services and the adoption of GRI has a positive influence. However, after several sensitivity tests, the results were mixed, and overall showed that GRI adoption did not improve the quality of disclosure. Thus, the research findings indicate that the use of external assurance services increases the quality of disclosure but there are still a lot of symbolic information in CSR disclosure in Indonesia, even though the company has already followed the GRI reporting framework.